Policy Implications of Community Volunteer Organizations as Development Catalyst and Governance Partner: The Case of Artist Groups in Angono, Rizal - Morales, Mark Anthony Mateo (Journal in Urban and Regional Planning; Vol 4 No 1 (2017): Journal in Urban and Regional Planning, 2021)
Robert Putnam shares that ‘volunteerism’ is necessary for building vibrant civil societies and in creating social capital networks of trust and cooperation that promote citizen participation in public affairs (Smith 1999). It also improves the quality of governance by refraining from precautionary or unnecessary state provision and administration of services that civic associations are equally capable of performing, if not better. Moreover, it is believed that these volunteer groups serve as assets to call on during a crisis. Using social capital growth will enable a stronger position in dealing with poverty and vulnerability (Putnam 2002). There is value in understanding how volunteer groups contribute to supporting programs and projects. They do not only improve the capacities of the government, but also the quality of life of people who are in most need of assistance. In the municipality of Angono, Rizal, a collaboration between the local government and volunteer groups highlights cultural expression through art as a development catalyst. As a governance tool, this benefits partner communities, thus enhancing Angono’s art-based tourism agenda and overall competitiveness. This paper discusses the challenges and opportunities of art as a development catalyst and governance tool for collaboration. The author interviewed local officials and group leaders from art-engaged community groups to find out how collaboration helps the poor members of Angono and its contribution to the development of the municipality. In studying the mutual benefits of the relationship between the local government and community-based groups, the study explored ways to increase the scope of engagement in cities to develop a broader societal base that promotes progress.
Keywords: volunteerism, community, poor and marginalized sector, cultural development, art